The Role of Religious Moderation in ELT: A Systematic Literature Review on Language, Identity, and Intercultural Understanding - Rasmin, La Ode; Pelu, Hanafi (Journal for Teaching and Education for Scholars, 2025)
This literature review evaluates the impact of religious moderation on English Language Teaching (ELT) in terms of its effects on language acquisition, identity change, and intercultural relations. Despite the growing attention to religious moderation in education, there remains a glaring gap in the literature regarding its application in ELT contexts. The analysis was conducted on published peer-reviewed articles, book chapters, and conference papers from major Scopus, Web of Science, ERIC, and Google Scholar databases within the past ten years. The review employed thematic analysis to identify patterns and trends in the moderation of religion in teaching English as a foreign language. The research results demonstrate three notable features. Firstly, religious moderation in pedagogy in ELT enhances religious student engagement through intercultural communicative competence pedagogy. Secondly, students attending ELT classes with a moderate religious atmosphere show greater positive outcomes in identity change, including increased motivation to learn English. These results highlight how religious moderation can foster tolerant, inclusive, and culturally sensitive ELT practices that promote social harmony worldwide. The review, however, admits many limitations, such as its regional scope and the paucity of empirical investigations. The educational effects of religious moderation in ELT should be assessed through classroom-based and longitudinal studies in the future, especially in a variety of institutional and cultural contexts.